Strategi komunikasi public relation melalui media sosial dalam meningkatkan engagement dan citra bank syariah indonesia - Nisa, Siti Khoirun (Maliki Interdisciplinary Journal, 2025)
The development of information technology has brought significant changes to the communication strategies of financial institutions, including Islamic banking. In the digital era, social media has become a crucial tool for strengthening relationships between institutions and the public. Bank Syariah Indonesia (BSI), a merger of three major Islamic banks, has utilized social media as a key instrument in its public relations (PR) strategy. This article synthesizes the findings of five previous studies on the implementation of digital PR communication strategies at BSI and Islamic financial institutions in Indonesia. The synthesis shows that social media serves not only as a promotional tool but also as a space for education, interaction, and strengthening the institution’s image. Through a targeted digital PR strategy, BSI has been able to increase customer engagement, expand market reach, and foster public trust in the Islamic financial system. Although still facing challenges such as reputational risks and misuse of information, ethical use of social media based on Islamic principles has proven effective in strengthening the institution’s positive image.